Optimization Of phenolic compounds and antioxidant extraction from Piper betle Linn. leaves using pressurized hot water - Nur Lailatul Rahmah; Mustapa Kamal, Siti Mazlina; Sulaiman, Alifdalino; Taip, Farah Saleena; Siajam, Shamsul Izhar (Tamkang University, 2022)
Piper betle Linn. (PBL) leaves is a medical plant commonly available in Malaysia, Indonesia, and other South and Southeast Asia countries. It contains high phenolic compounds, which allows it to be used as remedies that can treat many infectious diseases and is considered safe and cost-effective as a medicine. However, PBL leaves are a perishable commodity that requires an extraction process to obtain the benefit. A green process called pressurized hot water extraction (PHWE) can potentially extract the phenolic compounds from PBL leaves. There are many kinds of research related to PBL leaves, but lack of focus on the extraction optimization of phenolic compounds and antioxidants from PBL leaves using PHWE. This research aims to optimize the PHWE process of phenolic compounds and antioxidants from PBL leaves using Response Surface Methodology (RSM) - Box-Behnken Design (BBD). The RSM-BBD consisted of three dependent variables (process parameters), namely time (5-25 min), temperature (150-250oC), and solid loading (5-15%) at a pressure range of 0.4761-3.9760 MPa. The responses for the optimization were total phenolic content (TPC) and antioxidant activity. The optimal conditions were achieved at 210oC, 5 min, and 15% solid loading, producing 8.079 mg GAE/g of TPC and 92.561% of antioxidant activity. The validation shows that the predicted values are 83% (TPC) and 99.52% (antioxidant activity) compared to actual data. This result indicates that PHWE is a potential extraction method to extract phenolic compounds and antioxidants from PBL leaves.